2019
DOI: 10.1038/s41433-019-0466-3
|View full text |Cite
|
Sign up to set email alerts
|

Faden operation in consecutive esotropia

Abstract: Purpose To evaluate the efficacy of Faden procedure for correcting consecutive esotropia (ET). Methods This retrospective study included 25 children who developed consecutive ET after primary bilateral lateral rectus (BLR) recession and underwent medial rectus (MR) recession with the Faden procedure (Faden group) or MR recession only (control group) between 2013 and 2018. Postoperative deviation angles were evaluated at each follow-ups until postoperative 6-month visit. Surgical motor and sensory outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In this study as well as in a previous study 8 , MR recession with the Faden operation showed excellent surgical results in all patients with CET. In 24 months of follow-up after surgery, the patients who underwent MR recession with the Faden operation maintained stable alignment and good stereoacuity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this study as well as in a previous study 8 , MR recession with the Faden operation showed excellent surgical results in all patients with CET. In 24 months of follow-up after surgery, the patients who underwent MR recession with the Faden operation maintained stable alignment and good stereoacuity.…”
Section: Discussionsupporting
confidence: 86%
“…Kim et al 8 reported the surgical results of MR recession with the Faden operation for CET at 6 months postoperatively, which the patients maintained orthophoria and good stereoacuity (60 or better seconds of arc) at the final visit. In the present study, all patients in the Faden group had maintained orthophoria and good stereoacuity (60 or better seconds of arc) at postoperative 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation